2008
DOI: 10.1111/j.1742-4658.2008.06378.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐induced conformational transition of the amyloid core fragment Aβ(28–35) and its A30G and A30I mutants

Abstract: The interaction of the b-amyloid peptide (Ab) with neuronal membranes could play a key role in the pathogenesis of Alzheimer's disease. Recent studies have focused on the interactions of Ab oligomers to explain the neuronal toxicity accompanying Alzheimer's disease. In our study, we have investigated the role of lipid interactions with soluble Ab(28-35) (wild-type) and its mutants A30G and A30I in their aggregation and conformational preferences. CD and Trp fluorescence spectroscopic studies indicated that, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…In contrast, zwitterionic phospholipids, such as phosphatidylcholine (PC) or sphingomyelin, were reported in some studies to show very weak or no interaction with Aβ peptides and induce little if any ordered secondary structure (Terzi et al 1997 ;Chauhan et al 2000 ;Matsuzaki 2007 ;Chi et al 2008 ;Nagarajan et al 2008 ). In contrast, other studies showed signifi cant effects of PCs on the secondary structure and aggregation of Aβ; this includes our own work described in Sect.…”
Section: Interactions Of Aβ With Lipids Surfaces: Electrostatic Effectsmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, zwitterionic phospholipids, such as phosphatidylcholine (PC) or sphingomyelin, were reported in some studies to show very weak or no interaction with Aβ peptides and induce little if any ordered secondary structure (Terzi et al 1997 ;Chauhan et al 2000 ;Matsuzaki 2007 ;Chi et al 2008 ;Nagarajan et al 2008 ). In contrast, other studies showed signifi cant effects of PCs on the secondary structure and aggregation of Aβ; this includes our own work described in Sect.…”
Section: Interactions Of Aβ With Lipids Surfaces: Electrostatic Effectsmentioning
confidence: 89%
“…Numerous biophysical studies have demonstrated that lipids and lipid-mimicking detergents can importantly infl uence the secondary structure of Aβ and its aggregation and fi brillation in vitro. Thus, studies using NMR, circular dichroism, Fourier transform infrared spectroscopy, molecular dynamics simulations and fl uorescence spectroscopy have demonstrated Aβ interactions with vesicles containing anionic phospholipids such as phosphatidylglycerol (Terzi et al 1997 ;McLaurin et al 1998 ;Nagarajan et al 2008 ), as well as with other lipid assemblies such as bilayers, micelles or ganglioside clusters (Matsuzaki and Horikiri 1999 ;Mandal and Pettegrew 2004 ;Xu et al 2005 ;Matsuzaki 2007 ;Miyashita et al 2009 ;Matsuzaki et al 2010 ), and showed that these interactions can alter the secondary and/or the quaternary structure of the peptide.…”
Section: Interactions Of Aβ With Lipids Surfaces: Electrostatic Effectsmentioning
confidence: 97%
“…Increase in ThT fluorescence with time (days/h) was plotted mutant, an increase in energy transfer was noted upon binding to PG vesicles, as indicated by a decrease in Trp fluorescence intensity and a concurrent increase in dansyl fluorescence emission intensity. In a recent report, we have provided one possible explanation for the observed increase in energy transfer in the case of PG vesicles (Nagarajan et al 2008). Briefly, in the case of the E22G mutant, aggregation occurs in an alternative manner due to the spontaneous formation of β-sheet aggregates bound to the membrane.…”
Section: Fret Assaysmentioning
confidence: 94%
“…Ab (28)(29)(30)(31)(32)(33)(34)(35) having the sequence KGAIIGLM is a particularly attractive system as it is the key hydrophobic region and forms a rigid amyloid core of the full length Ab (Ippel et al, 2002). In a recent work (Nagarajan et al, 2008), we have examined the role of lipid interactions with soluble Ab(28-35) and its mutants A30G and A30I in their aggregation and conformational preferences. CD and Trp fluorescence spectroscopic studies reveal that these peptides adopt a random coil structure, immediately on dissolution.…”
Section: Introductionmentioning
confidence: 98%